1991
DOI: 10.1597/1545-1569(1991)028<0279:qsoaac>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire Survey of Attitudes and Concerns of Patients with Cleft Lip and Palate and Their Parents

Abstract: The self-perceived problems and concerns of patients with complete unilateral cleft lip and palate and their parents were investigated. Thirty-two patients ranging in age from 16 to 25 years (mean = 19.9 years) and their parents were sent questionnaires by mail. Twenty-eight patients and 30 parents completed the questionnaires. The results suggest that the patients were satisfied with the treatment they had received. They believed that the efforts of the members of the cleft palate team had been successful, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 0 publications
3
47
1
1
Order By: Relevance
“…For the child, looking and/or sounding different to their peers may interfere with social interaction and invite some degree of teasing or bullying (Hearst, 2007). Difficulties surrounding emancipation from the family unit and the initiation of intimate relationships may also be problematic (Noar et al, 1991;Danino et al, 2005). For prospective parents, decision making around starting or expanding a family may evoke distress due to the recurrence risk (Stock and Rumsey, in press).…”
Section: Impacts Of Cleftmentioning
confidence: 99%
“…For the child, looking and/or sounding different to their peers may interfere with social interaction and invite some degree of teasing or bullying (Hearst, 2007). Difficulties surrounding emancipation from the family unit and the initiation of intimate relationships may also be problematic (Noar et al, 1991;Danino et al, 2005). For prospective parents, decision making around starting or expanding a family may evoke distress due to the recurrence risk (Stock and Rumsey, in press).…”
Section: Impacts Of Cleftmentioning
confidence: 99%
“…In addition to the cognitive deficits, social dysfunction has been identified repeatedly and in high frequency in individuals with ICLP, as recently reviewed [38]. In general, individuals with ICLP are more likely to be socially inhibited or shy and report fewer friends than noncleft controls [17,31,41,42,50,58]. They are also less likely to join clubs or societies in school and less likely to marry [19,48].…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that these patients might experience a loss of self-image and selfesteem 5,7,23 , anxiety, depression, and social stigma throughout their lives 5,7,23 . These psychosocial effects may affect educational, career, and social opportunities 16,24 . Psychosocial outcome studies for patients with CL/P suggested that the influence of the family on the children's perception of their CL/P is paramount in the development of children's self esteem and perception of their condition 23 .…”
mentioning
confidence: 99%